A new species of square-headed wasp Dasyproctus Lepeletier & Brullé (Hymenoptera: Crabronidae: Crabronini) from India, with notes on its biology - Binoy, C.; Kumar, P. Girish; Santhosh, S. (Zootaxa, 2021)
Dasyproctus geethae Binoy & Girish Kumar sp. nov. is described with illustrations of both sexes, and of preimaginal stages with notes on its biology and ethology. New prey records of Diptera of the families Drosophilidae, Hybotidae, Stratiomyidae and Dolichopodidae are recorded for the genus.